2022
DOI: 10.1186/s12893-022-01698-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on hernia surgery in a Swedish healthcare region: a population-based cohort study

Abstract: Background Swedish healthcare has been reorganised during the COVID-19 pandemic, affecting the availability of surgery for benign conditions. The aim of this study was to determine the effects of COVID-19 on emergency and elective hernia surgery in a Swedish healthcare region. Methods Using procedure codes, data from inguinal and ventral hernia procedures performed at the three hospitals in Jönköping Region, Sweden, from March 1st 2019 to January 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The authors concluded that there was a 24% increase in emergency inguinal hernia repairs during the COVID-19 pandemic lockdown despite the overall reduction in emergency hernia repairs [ 17 ]. Other studies based in Sweden [ 9 ] and Turkey [ 17 ] either showed no changes in the number of emergency inguinal repairs or found a decrease of emergency inguinal repairs during the COVID-19 period respectively. However, both aforementioned studies found that the number of emergency ventral hernia repairs increased during the COVID-19 pandemic period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors concluded that there was a 24% increase in emergency inguinal hernia repairs during the COVID-19 pandemic lockdown despite the overall reduction in emergency hernia repairs [ 17 ]. Other studies based in Sweden [ 9 ] and Turkey [ 17 ] either showed no changes in the number of emergency inguinal repairs or found a decrease of emergency inguinal repairs during the COVID-19 period respectively. However, both aforementioned studies found that the number of emergency ventral hernia repairs increased during the COVID-19 pandemic period.…”
Section: Discussionmentioning
confidence: 96%
“…COVID-19 had a far-reaching impact on the health care system, forcing a widespread reallocation of resources and medical personnel [ 6 8 ]. This resulted in the postponement of many operations for benign conditions [ 9 11 ]. It is estimated that worldwide, more than 2 million operations were delayed per week during the first wave of the pandemic, the majority of which were planned [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a baseline decrease was reported in the elective scheduled surgeries in early 2020 as the result of governmental counteracts, 7 also with a consequent modification of the selection criteria of patients on the waiting list 8 . On the other hand, a steady curve before and during the pandemic regarding the number of urgent hernioplasty has been also reported 9 . Lastly, some authors suggested that in mildly symptomatic patients a safe management of the waiting list was obtained through the assessment of analgesic consumption and anamnestic frailty 10 …”
Section: Discussionmentioning
confidence: 99%
“…8 On the other hand, a steady curve before and during the pandemic regarding the number of urgent hernioplasty has been also reported. 9 Lastly, some authors suggested that in mildly symptomatic patients a safe management of the waiting list was obtained through the assessment of analgesic consumption and anamnestic frailty. 10 During the pandemic time, it was debated the feasibility of the Taxis maneuver in order to procrastinate as much as possible on the hernia correction presented in an emergency setting, in most cases at the expense of a worsened quality of life perception and patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also observed a decrease in elective hernia load without a corresponding increase in emergency hernia load. Kollatos et al 16 described how the overall number of emergency hernia repairs did not increase during the COVID-19 period in their healthcare region despite a decrease in elective procedures. Other studies [17][18][19] have also described decreased emergency hernia surgery rates during the pandemic.…”
Section: Hernia Cases (Elective and Emergency)mentioning
confidence: 99%